Strategi Kepemimpinan Kepala Madrasah dalam Meningkatkan Kedisiplinan dan Karakter Religius Siswa di MTSN 4 Karawang - Aulia Siti Aminah; Astuti Darmiyanti; Taufik Mustofa (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This research is grounded in the significant role of the madrasah principal in shaping students’ discipline and religious character as part of the goals of Islamic education. MTsN 4 Karawang was selected as the research site because it has various routine programs focused on habituation and character development. However, the implementation of these programs is not free from challenges. Therefore, a deeper study is needed to understand the leadership strategies applied by the principal in managing student discipline and religious activities at the school. The purpose of this study is to describe the leadership strategies used by the madrasah principal to improve student discipline, explain the principal’s role in developing students’ religious character, and identify the supporting and inhibiting factors in implementing these strategies. This study uses a qualitative method with data collected through observations, interviews, and documentation. The main informant of the research is the school principal. The collected data were reduced, presented in narrative form, and analyzed to identify patterns and meanings from the field findings. The results show that the principal applies transformational and participatory leadership through role modeling, religious habituation, and the involvement of teachers and students in monitoring discipline. The main supporting factors come from teacher collaboration, the student council (OSIS), and effective communication with parents